Climate crisis and children. A critical analysis of previous studies - Sánchez, Doris (2025)
The international literature on the climate crisis and childhood is vast worldwide; however, its relationship with Indigenous peoples is still precarious, considering that if its effects are disastrous in urban areas, their effects would be devastating for Indigenous children. We believe that further research is warranted. For this study, we have tracked and compiled 80 publications from diverse backgrounds and critically and meaningfully analyzed 36 ad hoc references. Our objective is to produce a systematized document, with information from the last 10 years, that will serve as a basis for constructing differentiated indicators within the framework of the climate crisis and its effects on Indigenous children in Peru and beyond. The specific objectives are: To systematize and analyze the information based on the tracking of 80 references and, based on this, analyze the 36 references found. To systematize and analyze information by economic sectors addressed by the different references, on the geographical location of the reviewed research, and on the various sectors addressed in the reviewed research. We used a qualitative methodology based on documentary analysis and descriptive statistics. The results of the systematic review revealed that only 25% of the data were related to Peru. We concluded that the level of education on the topic in Peru was precarious. Therefore, it is necessary to conduct fieldwork to investigate the impact of the climate crisis and its effect on the children of Indigenous peoples in Peru, based on previous studies. This will contribute to motivating research to seek solutions to its effects on the health, education, and nutrition of Indigenous children.